KUALITAS PELAYANAN PROGRAMPELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DIKECAMATAN LIMPUNG DAN BANDAR KABUPATEN BATANGTAHUN 2015-2016 - Abiyoga Wisnu Ahimsa; Muhammad Adnan (Journal of Politic and Government Studies, 2019)
Batang Regency, as a district that organizes regional governments that have an obligation to serve their citizens. The Government is very aware of the benefits of this policy is very big, for that they must immediately implement this policy to improve the quality of public services in Batang. This policy was implemented in 2015 with the issuance of Perbup Number 3 of 2015 Partial Delegation of Affairs that Becomes the Authority of the Regent to the District Head in the District Government and the District Head Regulation Number 77 of 2015 concerning Amendment to the Regent's Regulation Number 3 of 2015 concerning Partial Delegation Authority of District Head to District Head in Batang District Government. Broadly speaking, the District Integrated Administration Services program (PATEN) in Batang District, especially in Limpung and Bandar has been going well. Coordination between the Government of Batang and Kecamatan has gone well. Improving the quality of service in the District increasingly looks efficient and good so that makes the community feel comfortable in getting service. The perceived impact of the community regarding the implementation of the PATEN Program in Batang, especially in Limpung and Bandar, can be concluded that the community is satisfied with the public service they receive.Keywords: Quality, Service, PATEN